2006
DOI: 10.1007/s00395-005-0582-z
|View full text |Cite
|
Sign up to set email alerts
|

The antiatherogenic and antiinflammatory effect of HDL–associated lysosphingolipids operates via Akt ➞NF–kappaB signalling pathways in human vascular endothelial cells

Abstract: Adhesion of mononuclear cells to the vascular endothelium and their subsequent transmigration into the arterial wall represent key events in the pathogenesis of arteriosclerosis. In previous studies we have shown that high density lipoproteins (HDL) and the HDL-associated sphingosylphosphorylcholine (SPC) have the ability to suppress the TNF-alpha-induced expression of endothelial cell E-selectin. However, the current understanding of the mechanism by which HDL reduces the expression of E-selectin is still inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In addition to anti-atherosclerotic effects, HDL also has an anti-inflammatory role in macrophages and endothelial cells by inhibiting the expression of adhesion molecules (52,53). HDL activates Akt protein kinase to reduce the expression of E-selectin, intercellular cell adhesion molecule-1 and vascular cell adhesion protein 1, and thereby inhibits the function of tumor necrosis factor α to activate nuclear factor-κB in the nucleus, which has an anti-inflammatory role (54).…”
Section: The Function Of Hdlmentioning
confidence: 99%
“…In addition to anti-atherosclerotic effects, HDL also has an anti-inflammatory role in macrophages and endothelial cells by inhibiting the expression of adhesion molecules (52,53). HDL activates Akt protein kinase to reduce the expression of E-selectin, intercellular cell adhesion molecule-1 and vascular cell adhesion protein 1, and thereby inhibits the function of tumor necrosis factor α to activate nuclear factor-κB in the nucleus, which has an anti-inflammatory role (54).…”
Section: The Function Of Hdlmentioning
confidence: 99%
“…Inflammation and adhesion of mononuclear cells to the vascular wall are critical for AS initiation and development [36]. Inflammatory cytokines are important in the formation of lesional plaques and affect the entire atherosclerotic vessel [37].…”
Section: Resultsmentioning
confidence: 99%
“…SPC could also regulate the inflammation pathway in HUVECs. HDL-associated SPC had the ability to suppress the TNF-α-induced expression of endothelial cell E-selectin and the translocation of NF-κB into the cell nucleus [41]. This process was mediated through the activation of the PI3K/Akt pathway.…”
Section: Spc In Vesselsmentioning
confidence: 96%
“…Multiple studies in vitro have shown its pronounced influence on vessel pathology [40]. However, unlike S1P, many studies drew conflicting conclusions about the role of SPC in apoptosis and the inflammation of vessel cells [8,41]. Thus, whether SPC is beneficial or detrimental to atherosclerosis remains undetermined.…”
Section: Spc In Cardiovascular Disease Spc Relieves Myocardial Infarcmentioning
confidence: 99%